Neither balance nor bandwagon: South American international society meets Brazil's rising power - Merke, Mario Federico (2015)
This article examines the strategic positioning of Brazil in South America and how South America relates to Brazil's rising status both globally and regionally. It does so from the perspective of international society known as the English school. This perspective emphasizes how Brazil shares a number of values and institutions with its neighbors that offer the foundations for a distinct regional international society in South America. It thus challenges the materialist stance held by realism which envisages that secondary powers either balance or bandwagon the dominant pole and affirms instead that South America's strategies towards Brazil are more complex and nuanced than a simple polarity standpoint suggests.